2007
DOI: 10.1021/ol0705503
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharide Synthesis in Microreactors

Abstract: Described is the combination of microreactors and fluorous phase chemistry to assemble oligosaccharides. The synthesis of a beta-(1-->6) linked D-glucopyranoside homotetramer serves to illustrate this approach. Glycosylations employing a Fmoc-protected glucosyl phosphate building block were performed in a silicon-based micro-structured device to optimize reaction conditions and for reaction scale-up. A perfluorinated linker at the reducing end of the oligosaccharides allowed for purification by fluorous solid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(35 citation statements)
references
References 11 publications
0
35
0
Order By: Relevance
“…Other remarkable improvements in oligosaccharide synthesis have also emerged, including one-pot protection [89] and glycosylation strategies [50, 51, 90], polymer-supported [9193] and automated synthesis [94, 95], fluorous tag assisted synthesis in microreactors [96], and surface-tethered iterative carbohydrate synthesis (STICS) [97]. The chemoselective strategy, however, is still occupying an important niche in the arsenal of available methods.…”
Section: Discussionmentioning
confidence: 99%
“…Other remarkable improvements in oligosaccharide synthesis have also emerged, including one-pot protection [89] and glycosylation strategies [50, 51, 90], polymer-supported [9193] and automated synthesis [94, 95], fluorous tag assisted synthesis in microreactors [96], and surface-tethered iterative carbohydrate synthesis (STICS) [97]. The chemoselective strategy, however, is still occupying an important niche in the arsenal of available methods.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, fluorous protecting groups (groups incorporating a fluorinated alkyl chain) allow for the separation of fluori nated species (typically glycosyl acceptors) from nonfluorinated species ( glycosyl donors) by simple partitioning between perfluorohexanes and methanol (or toluene) [136]. Solution-based microreactors, developed in the late nineties, have been adapted to the fluorous tag-supported synthesis of oligosaccharides by Seeberger and co-workers [137]. A five-port silicon microfluidic reactor was utilized for the synthesis of the homotetramer (52).…”
Section: Automation Of the Fluorous Tag-supported Synthesismentioning
confidence: 99%
“…A five-port silicon microfluidic reactor was utilized for the synthesis of the homotetramer (52). For this purpose, a glycosyl phosphate donor (48) was first glycosidated with a fluorous linker (49) in the presence of TMSOTf [137]. To accomplish the glycosylation reaction in a microfluidic device, three separate solutions in dichloromethane were prepared: glycosyl acceptor, phosphate donor, and the activator (TMSOTf).…”
Section: Automation Of the Fluorous Tag-supported Synthesismentioning
confidence: 99%
“…[68][69][70] The authors reported for the first time the synthesis of higher oligosaccharides in a micro-device with microchannels 200 µm wide, 200 µm deep, and 40 cm long. The reaction between p-nitrophenyl-β-D-glucopyranoside (PNPGal) and ni trophenyl-2-acetamide-2-deoxy-β-D-glucopyranoside (PNPGlcNAc) was performed using β-galactosidase (from Escherichia coli) (Scheme 9).…”
Section: Oligosaccharidesmentioning
confidence: 99%